Dynamics of Development of Islamic Marketing Research: A Bibliometric Review Based on Scopus Data, 1998 - 2023 - Roudlotul Badi'ah; Dadang Wiratama; Ika Purwanti; Muhammad Dzikri Abadi (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
Islamic marketing is not just a trend but a global phenomenon that continues to grow. By focusing on Islamic values, product and service diversification, and the use of technology, Islamic marketing can bring positive change to the business world and Muslim society. This research analyzes publication performance, main themes, and trends in Islamic marketing literature. This research utilizes quantitative descriptive methods with a bibliometric approach. Data sources were obtained from the Scopus database and analyzed using VOSviewer and Biblioshiny software. Findings show 274 research documents on Islamic marketing in the Scopus database during the 1998-2023 period. Malaysia and the International Islamic University Malaysia are the most active in publishing this research. Many publications regarding Islamic marketing focus on the Journal of Islamic Marketing and the disciplines of Business, Management, and Accounting. Over the last 25 years, Islamic marketing research in the Scopus database has emphasized aspects of Islamic marketing among Muslim consumers. The latest research opportunities in Islamic marketing include halal markets, halal tourism, Islamic hospitality, Islamic market segmentation, and Muslim consumers.